Karakteristik bidang gelincir di Kecamatan IX Koto Sungai Lasi Kabupaten Solok berdasarkan metode geolistrik tahanan jenis konfigurasi Schlumberger (Characteristics of the slip plane in IX Koto Sungai Lasi Subdistrict, Solok Regency based on the geoelectric resistivity method of the Schlumberger configuration) - Dori Purnama Sari; - Akmam (Department of Physics – Universitas Negeri Padang UNP, 2019)
Landslide is which one frequent disaster that caused by weathered soil which is characterized by the existence of slip surfaces. The aims of the research were to find out the shape, depth, and slope angle of slip surface at Sungai Lasi Solok base on Geoelectric Data. Data were collected by Automatic Resistivity System Multi-electrode. The interpretation of the Geoelectric data was used Two Dimensions Smoothness Constraint Least-Square Inversion Method. The slope angle of the slip surface was using the Trigonometry theory. The average results of the research are the shape, depth, and the slope angle of the slip surfaces are rotational slide for fisrt and second line and translational slide for third and fourth line, 32.2175 degrees and 11. 825 meters.